Partner Violence and Condom Use in HIV-Discordant Heterosexual Partnerships - Abigail Eaton; Ariane van Der Straten; Janet Saul; Stephen Shiboski; Nancy Padian (Journal of Clinical Research In HIV AIDS And Prevention, 2014)
This paper examines the association between intimate partner violence and the consistency of condom use in a US urban cohort of HIV-serodiscordant couples. It uses both male and female data from the California Partners Study II of a lower-income ethnically mixed cohort of 145 such couples in the San Francisco Bay Area. We observed a significant association between inconsistent condom use and physical abuse: the risk of inconsistent condom use was double for those experiencing physical abuse (OR, 2.2; 95% CI, 1.1, 4.1). Injection drug use and a history of bisexual behavior were also associated with inconsistent condom use. Physical abuse tended to be reciprocal between partners (OR, 3.2; 95% CI, 1.9, 5.6). Our findings suggest that interventions effective in reducing intimate partner violence, and/or reducing the use of injection drugs in HIV-serodiscordant couples could lead to less transmission of HIV.
Keywords: intimate partner violence